Revision of the non-marine centric diatom flora (Bacillariophyta) of the sub-Antarctic Campbell Island (southern Pacific Ocean) with the descriptions of five new species - Goeyers, Charlotte; van de Vijver, Bart (European Journal of Taxonomy, 2020)
During a survey of the moss-inhabiting diatom flora of the sub-Antarctic Campbell Island, located in the southern Pacific Ocean, several unknown centric diatoms were observed that could not be identified using the currently available literature. Detailed light and scanning electron microscopical observations and comparisons with the characters of several species of Melosira, Angusticopula, Ferocia and Arcanodiscus worldwide indicated that five of them should be described as new to science: Angusticopula cosmica Goeyers & Van de Vijver sp. nov., Arcanodiscus crawfordianus Goeyers & Van de Vijver sp. nov., A. indistinctus Goeyers & Van de Vijver sp. nov., A. saundersianus Goeyers & Van de Vijver sp. nov. and Ferocia houkiana Goeyers & Van de Vijver sp. nov. A sixth species, Angusticopula chilensis, was illustrated for the first time using SEM and as a result is considered to differ sufficiently from A. dickiei to warrant epitypification as A. chilensis. The new species were first described in genera that formerly were included within the genus Melosira. All six species are morphologically characterized and compared with similar species within their respective genera. Their presence and distribution on Campbell Island are discussed based on the observations made in the available samples.